Phenology and Morphometric Attributes of the Flower and Fruit of Cultivated Elaeocarpus angustifolius, the Rudraksha Plant from India - Singh, A. N. (Indian Forester, 2021)
The Elaeocarpus angustifolius Bl. (Syn. E. ganitrus Roxb. ex G. Don, E. sphaericus (Gaertn) K. Schume) occur naturally in various parts of India. The plant has poor regeneration in the wild and has been reported as a threatened species in the north-eastern region of India. This plant, known as Rudraksha in India, has been considered very sacred and pious for devotees in Hinduism. The descriptions made for this plant in the present article will further prove useful in correct identification of this plant. The input on phenological aspects will help in making strategies for conservation of this threatened and medicinally important Indian plant.